Spatial Genetic Structure of the Insect-Vectored Conifer Pathogen Leptographium wageneri Suggests Long Distance Gene Flow Among Douglas-fir Plantations in Western Oregon - Bennett, Patrick I.; Tabima, Javier F.; Leon, Anna L.; Browning, John; Wingfield, Michael J.; LeBoldus, Jared M. (Frontiers in Forests and Global Change, 2021)
Many fungi in the Ophiostomatales are vectored by bark beetles that introduce these fungi directly into their tree hosts. Most of these fungal associates have little effect on their hosts, but some can cause serious diseases. One such fungus, Leptographium wageneri, causes an economically and ecologically important tree disease known as black stain root disease. For this study, 159 full genome sequences of L. wageneri were analyzed using a population genomics approach to investigate the epidemiology, dispersal capabilities, and reproductive biology of this fungus. Analyses were performed with SNP haplotypes from 155 isolates of L. wageneri var. pseudotsugae collected in 16 Douglas-fir stands in Oregon and 4 isolates of L. wageneri var. wageneri collected in pinyon pine stands in southern California. These two host-specific varieties appear to be evolutionarily divergent, likely due a combination of factors such as host differentiation and geographic isolation. We analyzed gene flow and population structure within and among Douglas-fir plantations in western Oregon to infer the relative importance of local vs. long distance dispersal in structuring populations of L. wageneri var. pseudotsugae. Long-distance gene flow has occurred between Douglas-fir plantations, contributing to diversity and population structure within stands, and likely reflecting the behavior of an important insect vector. Genetic clustering analyses revealed the presence of unique local clusters within stands and plantations in addition to those common among multiple stands or plantations. Although populations of L. wageneri var. pseudotsugae are primarily asexual, two mating types were present in many stands, suggesting that recombination is at least possible and may contribute to genetic diversity.